(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2024)
In this work, end-quenched test apparatus that was locally produced was used to choose and prepare mild steel, cast iron, and stainless steel for hardenability testing. With an end-quenched machine, every sample was quenched with warmed water at 25 oC after being heated to 920 oC and soaked for full autenization. It was shown from the outcomes that the heat treatment had an effect on every material tested. The hardness (hardenability) of ferrous alloys diminishes with the increasing gradient of the Jominy curve. In every instance, the tip reaches the highest possible toughness. Stainless steel reacts extremely poorly to heat treatment using the Jominy End-Quenched process; however, mild steel and cast iron perform much better, as measured by the hardness at 0 mm depth in relation to the as-cast ferrous alloys. The performance of hardenability was consistent with the composition of each ferrous alloy. The information helps machinists identify ferrous alloys that require pre- and post-heating during welding and determine what sort of fluid to use for different ferrous alloy categories.